2008
DOI: 10.3748/wjg.14.4065
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonically activated scalpel versus monopolar electrocautery shovel in laparoscopic total mesorectal excision for rectal cancer

Abstract: AIM:To investigate the feasibility and safety of monopolar electrocautery shovel (ES) in laparoscopic total mesorectal excision (TME) with anal sphincter preservation for rectal cancer in order to reduce the cost of the laparoscopic operation, and to compare ES with the ultrasonically activated scalpel (US). METHODS: Forty patients with rectal cancer, who underwent laparoscopic TME with anal sphincter preservation from June 2005 to June 2007, were randomly divided into ultrasonic scalpel group and monopolar ES… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“… Colorectal surgery : The initial literature search revealed a total of 209 records identified through database searching, but only 7 studies fully matched the aim of this systematic review and were included in the final sample and relative analysis. Out of the 7 included studies, 4 were RCTs, and it was possible to perform quantitative synthesis [ 24 27 ]; the other 3 records were observational, two retrospective, and one prospective study [ 28 30 ]. In general terms, HEDs do not add substantial advantages in comparison to traditional energy devices in terms of primary (operative time, intra- and post-operation complications, intra-operatory blood loss) or secondary outcomes (time to discharge, conversion to open surgery).…”
Section: Resultsmentioning
confidence: 99%
“… Colorectal surgery : The initial literature search revealed a total of 209 records identified through database searching, but only 7 studies fully matched the aim of this systematic review and were included in the final sample and relative analysis. Out of the 7 included studies, 4 were RCTs, and it was possible to perform quantitative synthesis [ 24 27 ]; the other 3 records were observational, two retrospective, and one prospective study [ 28 30 ]. In general terms, HEDs do not add substantial advantages in comparison to traditional energy devices in terms of primary (operative time, intra- and post-operation complications, intra-operatory blood loss) or secondary outcomes (time to discharge, conversion to open surgery).…”
Section: Resultsmentioning
confidence: 99%
“…ES has been shown to be equally effective and safe as USD and more cost-effective than USD in randomised studies comparing use of ES with USD in laparoscopic colorectal surgeries and hysterectomies [12] , [27] , [28] . Monopolar ES instruments are available in different shapes, such as monopolar electrocautery knife, monopolar electrocautery hook, monopolar electrocautery scissors, and monopolar spatula, which can suit varied needs.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have reported a reduction in cost per procedure, as the use of USD allowed a reduced number of alternative disposable items to be used [8] , [31] . Whilst others have shown that the use of USD significantly increases the cost of the operation [27] , [28] . We avoid using costly disposables and mostly rely on use of reusable instruments.…”
Section: Discussionmentioning
confidence: 99%
“…This study showed no significant difference in blood loss, but ES may generate heavy smog. Furthermore, ES can produce a higher surface temperature when managing tissues [71].…”
Section: (100% [Strong Consensus]; Gor C: 100% [Strong Consensus])mentioning
confidence: 99%
“…After visualization of the left ureter, the IMA is dissected free and is divided between clips, endostapler or sealing device at high or low tie level. Low tie level will permit preservation of the left colonic artery and better protection of the hypogastric plexus on the aorta [71,[75][76][77][78][79][80][81][82][83][84][85][86][87][88].…”
Section: 7% [Consensus]; Gor A: 857% [Consensus])mentioning
confidence: 99%